Elevated Thyroid Peroxidase Antibody Increases Risk of Post-partum Depression by Decreasing Prefrontal Cortex BDNF and 5-HT Levels in Mice - Zhou, Yingying; Wang, Xinyi; Zhao, Yuhang; Liu, Aihua; Zhao, Tong; Zhang, Yuanyuan; Shan, Zhongyan; Teng, Weiping (Frontiers in Cellular Neuroscience, 2017)
Post-partum depression (PPD) is a common mental disease in the perinatal period that profoundly affects mothers and their offspring. Some clinical studies have found that PPD is related to thyroid peroxidase antibodies (TPOAbs); however, the mechanism underlying this relationship is unclear. Female C57BL/6 mice immunized with adenovirus encoding the cDNA of the full-length mTPO (mTPO-Ad) were used to establish the isolated TPOAb-positive mouse model in the present study. Maternal depressive-like behaviors were assessed using the forced swimming test (FST), sucrose preference test (SPT), and tail suspension test (TST) post-partum. The serum TPOAb titer was measured by enzyme-linked immunosorbent assay (ELISA) before pregnancy and post-partum. Furthermore, in the prefrontal cortex, the mRNA and protein expression levels of brain-derived neurotrophic factor (BDNF) were measured, serotonin (5-HT) levels were measured by ultra-high-performance liquid chromatography–tandem mass-spectrometry (UHPLC–MS/MS), and total thyroxine (TT4) levels were determined by ELISA. Compared with the controls, the mice immunized with mTPO-Ad displayed depressive behaviors, with a significantly lower sucrose preference (SP) at the 12-h time point and a longer immobility time in the FST and TST, which were accompanied by a lower expression of BDNF and 5-HT but no change in the TT4 concentration in the prefrontal cortex. Together, these findings suggest that elevated TPOAb may increase the risk of subsequent PPD and decrease the concentration of BDNF and 5-HT in the prefrontal cortex.